2019
DOI: 10.5535/arm.2019.43.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neuromuscular Electrical Stimulation for Masseter Muscle on Oral Dysfunction After Stroke

Abstract: ObjectiveTo determine positive effect of neuromuscular electrical stimulation (NMES) in conventional dysphagia therapy on masseter muscle oral dysfunction of patients after subacute stroke.MethodsAmong subacute stroke patients who were diagnosed as oropharyngeal dysphagia by videofluoroscopy swallowing study (VFSS), those with oral dysfunction were enrolled. They were randomly assigned to a study group or a control group. The study group received NMES on masseter muscle and suprahyoid muscle simultaneously, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…48,49 The possible explanation might be electrical stimulation can increase pharyngeal and laryngeal activities by increasing the contraction force of hyoid bone muscle. 50 A study done by Zeng et al (2018) 31 reported that NMES and swallowing rehabilitation training together may significantly improve swallowing function which was consistent with the results of two similar studies conducted by Park et al, 41 and Lim et al 51 A study done by Lee et al (2019) 38 suggested that the application of NMES on masseter muscle had a therapeutic effect on oral dysfunction of patients after sub acute stroke. This might be due to chewing functional activities of this muscle might play an important role in stimulating the initiation of the swallowing process.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…48,49 The possible explanation might be electrical stimulation can increase pharyngeal and laryngeal activities by increasing the contraction force of hyoid bone muscle. 50 A study done by Zeng et al (2018) 31 reported that NMES and swallowing rehabilitation training together may significantly improve swallowing function which was consistent with the results of two similar studies conducted by Park et al, 41 and Lim et al 51 A study done by Lee et al (2019) 38 suggested that the application of NMES on masseter muscle had a therapeutic effect on oral dysfunction of patients after sub acute stroke. This might be due to chewing functional activities of this muscle might play an important role in stimulating the initiation of the swallowing process.…”
Section: Discussionmentioning
confidence: 53%
“…Out of 11 studies, 10 of them (n=748) confirmed that NMES had increased swallowing function of post-stroke dysphagia patients compared to the control groups in all outcome measures. 30,[33][34][35][37][38][39][40] However, one study (n=36) indicated that the NMES had no observed differences between the experimental and control groups. 36…”
Section: Effects Of Nmes On Swallowing Functionsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is used in facilitation techniques to increase muscle strength and sensory awareness and to prevent muscle atrophy, thereby improving motor function [ 14 , 15 ]. Recently, several studies have demonstrated that NMES does not only induce the activation of the masticatory muscle [ 16 , 17 ] but is also effective for improving oral functions, including masticatory functions in the oral phase of the swallowing process [ 18 , 19 ], which might be due to cortical excitability and physiological changes induced by NMES.…”
Section: Introductionmentioning
confidence: 99%